2023
DOI: 10.7759/cureus.37576
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Infection Rates During the Pandemic in New York Capital Area: A Single-Center Study

Abstract: IntroductionClostridioides difficile (C. difficile) colonizes the large intestine, rendering healthy individuals asymptomatic carriers of the disease. In certain instances, C. difficile infection (CDI) occurs. Antibiotic use remains the leading risk factor for CDI. During the coronavirus disease 2019 (COVID-19) pandemic, multiple risk and protective factors for and against CDI were identified, and as such multiple studies tried to analyze the pandemic's overall effect on CDI incidence rates, with contradictory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…If in 2016 the number of cases was 1.73‰, it progressively increased to 9.81‰ in 2017, 14.36‰ in 2019, 16‰ in 2020, reaching the highest incidence of 22.02‰ in 2021, followed by a slight decline to 17.21‰ in 2022, and then 16.7‰. An increase in CDI incidence is reported in other studies, explaining that this rise is because of increased use of antibiotics and/or steroids, or even the modification of the patient population profile admitted during the pandemic [18,[27][28][29]. In another study, Markovic-Denic L reported that the incidence density rate was three times higher when the hospital was a dedicated COVID-19 hospital, meaning only COVID-19-positive patients were admitted, compared to the period when it was a non-COVID-19 hospital, before and during the COVID-19 pandemic [30].…”
Section: Discussionmentioning
confidence: 69%
“…If in 2016 the number of cases was 1.73‰, it progressively increased to 9.81‰ in 2017, 14.36‰ in 2019, 16‰ in 2020, reaching the highest incidence of 22.02‰ in 2021, followed by a slight decline to 17.21‰ in 2022, and then 16.7‰. An increase in CDI incidence is reported in other studies, explaining that this rise is because of increased use of antibiotics and/or steroids, or even the modification of the patient population profile admitted during the pandemic [18,[27][28][29]. In another study, Markovic-Denic L reported that the incidence density rate was three times higher when the hospital was a dedicated COVID-19 hospital, meaning only COVID-19-positive patients were admitted, compared to the period when it was a non-COVID-19 hospital, before and during the COVID-19 pandemic [30].…”
Section: Discussionmentioning
confidence: 69%
“…In line with our findings, a recently published paper indicated a trend similar to that of Clostridium difficile infections over a 5-year period (2018-2021). It revealed that the infection incidence rate increased from 5.67 +/− 0.35 before the onset of the pandemic to 8.06 +/− 0.41 in the 2020-2021 period (95% confidence interval) [18].…”
Section: Discussionmentioning
confidence: 99%